A qualitative phenomenological analysis of the subjective experience and understanding of the at risk mental state. Issue 1 (1st January 2017) - Brew, Benjamin; Shannon, Ciaran; Storey, Lesley; Boyd, Adrian; Mulholland, Ciaran
ABSTRACT: Over recent years there has been a growing interest in identifying the early stages of psychosis. The At Risk Mental State (ARMS) is characteristic of the prodromal stages of psychosis and its identification gives rise to a number of clinical and research opportunities including early intervention and prevention of psychosis. This study employs interpretative phenomenological analysis to gain insights into the subjective experience and individuals understanding of the development of their ARMS. Five participants took part and provided information on the experience of symptoms, life prior to onset of their ARMS and their understanding of symptoms and their development through a semi structured interview. From the analysis of transcripts eight themes emerged which were common across participants accounts. Three themes of experience (disturbed world/disturbed self, disconnection with the world, thunderstruck) and five themes of understanding (absence of understanding, use of others, identity, forming links, fragmented understanding) were identified. Themes are explored in detail and discussed in relation to existing literature and theory. Clinical implications, directions for future research, and limitations are discussed within.